State-of-the-Art Review on Recent Advancements on Lateral Control of Autonomous Vehicles - Archishman Biswas; M. A. Obayed Reon; Prangon Das; Zinat Tasneem; S. M. Muyeen; Sajal K. Das; Faisal R. Badal; Subrata Kumar Sarker; Md. Mehedi Hassan; Sarafat Hussain Abhi; Md. Robiul Islam; Md. Firoj Ali; et al. (IEEE Access, 2022)
The most well-known research on driverless vehicles at the moment is connected autonomous vehicles (CAVs), which reflects the future path for the self driving field. The development of connected autonomous vehicles (CAVs) is not only increasing logistics operations, but it is also opening up new possibilities for the industry’s sustainable growth. In this review, we will explore the cloud-controlled wireless network-based model of cyber physical aspect of the autonomous vehicle, which is coupled with unmanned aerial vehicles (UAVs). Additionally, this model is Internet of Things (IoT) managed and AI-based, with a blockchain-based security mechanism. Additionally, we’ll focus on lateral control in autonomous driving, particularly the lane change maneuver, taking social behavior into account. Here, we briefly reviewed Vehicle-to-Everything (V2X) communication, which is carried out by on-board sensors and connected wireless medium that enhance the lane departure processes while retaining human driver behavior relying on obstacle avoidance.